The Deflection Control of a Thin Cantilever Beam by Using a Piezoelectric Actuator / Sensor - Al-Ashtari, Waleed Khalid. (Nahrain University College of Engineering Journal, 2008)
In this research, the governing equation of the thin smart beam transverse deflection was derived by the same procedure that the Bernoulli-Euler equation derived but with some additional mathematical terms to be valid for describing the smart beam. The engineering control techniques were used to obtain the solution of the proposed differential equation for the smart cantilever beam where with some auxiliary equations and modifications a block diagram for any type of applied load (static, or cyclic) as the input and the beam deflection as the output was constructed. For insuring an efficient reduction in the beam deflection an integrated system with a voltage amplifier and lead controller was designed. Many cases were studied and simulated including the variation of load nature, and the number of collocated piezoelectric actuator/sensor pairs and in all cases a valuable deflection reductions were obtained